2017
DOI: 10.1038/nature23318
|View full text |Cite
|
Sign up to set email alerts
|

mRNA 3′ uridylation and poly(A) tail length sculpt the mammalian maternal transcriptome

Abstract: A fundamental principle in biology is that the program for early development is established during oogenesis in the form of the maternal transcriptome1,2. How the maternal transcriptome acquires the appropriate content and dosage of transcripts is not fully understood. Here we show that TUT4/7-mediated mRNA 3′ terminal uridylation sculpts the mouse maternal transcriptome by eliminating transcripts during oocyte growth. TUT4/7-mediated uridylation is essential for both oocyte maturation and fertility. In compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 43 publications
9
171
0
Order By: Relevance
“…We also observed that TUT4/7 knockdown partially blocks the increase of uridylation during Xenopus oocyte maturation ( Figures S4A and S4B). Thus, TUT4 and/or TUT7 are responsible for mRNA uridylation in fish and frog, as well as in mammals Morgan et al, 2017). Conversely, the splicing-blocking morpholinos had no detectable effect during these stages (data not shown), which is consistent with a previous report (Thornton et al, 2014).…”
Section: U Tails Emerge At the Onset Of The Mzt In Vertebratessupporting
confidence: 92%
“…We also observed that TUT4/7 knockdown partially blocks the increase of uridylation during Xenopus oocyte maturation ( Figures S4A and S4B). Thus, TUT4 and/or TUT7 are responsible for mRNA uridylation in fish and frog, as well as in mammals Morgan et al, 2017). Conversely, the splicing-blocking morpholinos had no detectable effect during these stages (data not shown), which is consistent with a previous report (Thornton et al, 2014).…”
Section: U Tails Emerge At the Onset Of The Mzt In Vertebratessupporting
confidence: 92%
“…However, although little Ccnb1 mRNA loading onto ribosomes was detected in GV-arrested oocytes, Ccnb2 mRNA loading was considerably higher. These indirect measures of translation were corroborated by mining data sets assessing the poly(A)-tail length of mRNAs in GV-arrested oocytes (Morgan et al, 2017). Ccnb2 mRNA had a significantly longer poly(A)-tail compared with Ccnb1 (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Several recent studies demonstrated that uridylation is a key factor in germline development, early embryogenesis and differentiation [30,74]. The expression of TUT4/7 is elevated during embryogenesis, which indicates their importance in development.…”
Section: (E) the Role Of Mrna Uridylation In Developmentmentioning
confidence: 98%
“…The expression of TUT4/7 is elevated during embryogenesis, which indicates their importance in development. TUT4/7 play a major role in the establishment of the mammalian maternal transcriptome during oogenesis [30]. Each stage of oogenesis expresses a specific transcriptome.…”
Section: (E) the Role Of Mrna Uridylation In Developmentmentioning
confidence: 99%
See 1 more Smart Citation